Experimental and Theoretical Insight into the Kinetics and Mechanism of the Synthesis Reaction of 2, 3‐Dihydro‐2‐phenylquinazolin‐4(1H)‐one Catalyzed in Formic Acid. Issue 3 (23rd January 2017) - Habibi‐Khorassani, Sayyed Mostafa; Shahraki, Mehdi; Ebrahimi, Ali; Darijani, Mahdieh
ABSTRACT: An efficient and simple method has been developed for the synthesis of 2, 3‐dihydro‐2‐phenylquinazolin‐4(1 H )‐one catalyzed in formic acid. Also, the synthesis reaction between benzaldehyde and 2‐aminobenzamid was monitored spectrally. On the basis of the kinetic data obtained by the UV–vis spectrophotometry, both the first and second steps of the speculative five steps mechanism were enabled to be a rate‐determining step and also reaction showed second‐order kinetics. Considering information obtained by the stopped‐flow technique indicated that the first step is certainly a fast step. Moreover, the reaction was energetically and thermodynamically evaluated using theoretical methods and results were profoundly compared with the experimental approaches. Herein, theoretical rate constants were obtained using potential energy surfaces and the transition state theory at the B3LYP/6–311+G** level of theory. The Winger method was also applied to describe the tunneling effects. Calculations showed that the second step was the rate‐determining step in accordance with the experimental data. It is also found that the oxidation step was the fastest step in the proposed mechanism. For all five steps, two possibilities were considered for generating the probable product by using the thermodynamic parameters and kinetic data. Thermodynamic parameters also showed an exothermic reaction.